Differences In Geography Learning Results Using The Nearpod Application on The Material Diversity of Flora Fauna in Indonesia Class XI Academic Year 2023/2024 SMA Negeri 21 Surabaya - Rully Ardiansyah; Aisy, Izdihar; Tria Lestari; Sri Murtini; Sukma Perdana Prasetya (International Journal of Geography, Social, and Multicultural Education, 2025)
Instructional media is a device that allows students to acquire information , knowledge , experience,  and  skill  in  teaching  and  learning    process.  The  problem  often  faced  by teachers in teaching is to choose appropriate instructional media in the learning process so  that  students  fully  understand  the  given  subject.  This  study  aimed  to  determine differences in cognitive learning outcomes of students after using gradual and thorough Nearpod  application  instructional  media  based  on  cognitive  load  theory  to  subject diversity of flora and fauna in Indonesia. This research is a quasi experimental factorial design with 2 × 1. Source of this study come from students , media specialists , and expert material obtained from the research questionnaire. Meanwhile learning outcomes data that is obtained through a pre-test and post-test .The results  based on the score of the student  post-test  shows  that  class  which  use  the  Nearpod  application  media    had  an average value of 90, better than class that use no instructional media which scored 74 so there  is  significant  differences  occurred  between  the  three  classesis  evidenced  in  the results of the Independent T Test results that have a Sig. 0,031 this suggests there is a difference , then H0 is rejected and H1 accepted . In other words, Nearpod application media influenced on student learning outcomes . Based on this study it is suggested that  the teacher can use a Nearpod application instructional media in teaching process